Factors Associated With Intention to Quit Among Male Smokers in Vietnam: Results From the Vietnam Population-Based Provincial Global Adult Tobacco Survey in 2022-2023 - Ngoc Bich Nguyen; Hoang Van Minh; Tran Thi Tuyet Hanh; Anh Kim Thi Le; Luong Ngoc Khue; Phan Thi Hai; Linh Thuy Nguyen; Duong Tu Anh; Thanh Quoc Pham; Thuy Thu Thi Tran; Linh Phuong Nguyen; Phan Van Can (Tobacco Use Insights)
Objective: This study seeks to extensively examine the intentions of Vietnamese male smokers to quit, delving into key factors associated with their inclination toward smoking cessation to gain insights to inform and enhance tobacco control initiatives in the country. Methods: The data in this cross-sectional study was informed by the Vietnam Provincial Global Adult Tobacco Survey (PGATS) 2022-2023. A total of 35 974 male smokers aged 15 years and older from 30 provinces and cities in Vietnam were surveyed regarding their intentions to quit. Data on the participants’ demographic characteristics, smoking habits, and smoking cessation attempts were collected and analyzed for their associations with quit intention using chi-square test and logistic regression. Results: Overall, 48.4% of current smokers expressed an intention to quit. Those residing in rural areas were less likely to report this intention (OR = 0.929, 95% CI = 0.862-1.000), while occasional smokers (OR = 1.672, 95% CI = 1.580-1.769) and individuals who delayed their first cigarette by more than 60 minutes after waking (OR = 1.710, 95% CI = 1.583-1.845) were more likely to express a desire to quit. Factors such as exposure to information on smoking hazards, health warnings on cigarette packages, and receiving advice from healthcare professionals also significantly increased quit intentions. In contrast, those who had not attempted to quit in the past 12 months were much less likely to express a desire to quit (OR = 0.125, 95% CI = 0.116-0.134). Conclusion: This study underscored the complex interplay of demographic, behavioral, and informational factors associated with the intention of Vietnamese male smokers to quit. These findings contribute to Vietnam’s tobacco control efforts by guiding policymakers and public health authorities in refining smoking cessation programs, enhancing effectiveness of smoking interventions, ultimately reducing smoking prevalence and improving public health outcomes in Vietnam.